2015
DOI: 10.1108/jaar-03-2012-0018
|View full text |Cite
|
Sign up to set email alerts
|

Board monitoring and internal control system disclosure in different regulatory environments

Abstract: Purpose\ud – The purpose of this paper is to investigate two research questions. Is internal control system (ICS) disclosure, as a monitoring mechanism, associated with the characteristics of the board of directors, particularly the audit committee as the main board committee devoted to the effectiveness of ICS? Does the regulatory environment, particularly the regulation on ICS disclosure as an external governance/monitoring mechanism play a role in shaping the relationship between board monitoring and ICS di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 57 publications
3
50
1
1
Order By: Relevance
“…We also control for the other CEO characteristics. Previous studies have found a significant association between the other CEO characteristics (such as tenure, duality, and gender) and ICWs (Lin et al, ; Michelon et al, ; Yazawa, ). If CEOs' financial expertise is correlated with these characteristics, then our results may be biased due to an omitted‐variable problem.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We also control for the other CEO characteristics. Previous studies have found a significant association between the other CEO characteristics (such as tenure, duality, and gender) and ICWs (Lin et al, ; Michelon et al, ; Yazawa, ). If CEOs' financial expertise is correlated with these characteristics, then our results may be biased due to an omitted‐variable problem.…”
Section: Resultsmentioning
confidence: 93%
“…Given the consequences of ICWs, researchers have extensively explored the determinants of ICWs, such as firm‐level factors (e.g., firm size, age, complexity, growth, diversification, and corporate governance) and external factors (e.g., external auditor, regulations, and national culture; see Chalmers, Hay, & Khlif, , for a review). In particular, previous studies have documented the link between ICWs and management‐level factors, such as CEO entrenchment, age, and gender (Lin, Wang, Chiou, & Huang, ); CEO duality (Michelon, Bozzolan, & Beretta, ); and CEO tenure (Yazawa, ). However, to the best of our knowledge, the link between CEOs' financial background and ICWs remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Since FLID capture current plans and future forecasts (Hussainey et al, 2003), the lack of sufficient FLID may end up with volatile stock prices and uncertainty in investments. The "traditional" reporting, largely based on financial statements has been questioned in terms of its ability to meet the increasing information needs (Michelon et al, 2015). It is quite challenging for many users understand the elements of financial statements without narrative explanations due to the increasing complexity of regulations, business contexts, firm's strategies and operations makes.…”
Section: Gender Diversity On the Board And Voluntary Disclosurementioning
confidence: 99%
“…In fact, narrative disclosures contribute not only through the clarification of quantitative and financial measures but also through the identification of value-generation drivers not represented well in the financial statements (e.g. Schleicher et al, 2007;Souabni, 2011;Michelon et al, 2015).…”
Section: Gender Diversity On the Board And Voluntary Disclosurementioning
confidence: 99%
“…The mandatory reporting of environmental and social matters has come a very long way in a relatively short time. However, subject to management discretion and incentives, mandated disclosure can be either a substantial source of information that is useful in supporting investors’ and stakeholders’ judgment, or simply a formal box‐ticking task (Michelon, Bozzolan, and Beretta, ).…”
mentioning
confidence: 99%